Kerusakan Deoxyribonucleic Acid (DNA) Spermatozoa Memengaruhi Tingkat Kebuntingan Sapi Brahman (DAMAGE TO DEOXYRIBONUCLEIC ACID (DNA) SPERMATOZOA AFFECTING THE LEVEL OF PREGNANCY IN BRAHMAN CATTLE) - Priyanto, Langgeng; Budiyanto, Agung; Kusumawati, Asmarani; Kurniasih, Kurniasih (Jurnal Veteriner; Vol 20 No 1 (2019)DO - 10.19087/jveteriner.2019.20.1.119, 2019)
The relationship among of sperm DNA damage in cows with pregnancy rates has not been widely studied. The purpose of this study to determine the relationship of sperm DNA damage with pregnancy rate on Brahman cows. The sperm DNA damage rate was measured by Sperm-BosHalomax® from 2 samples of male Brahman bull straw (40002 and 40885) and pregnancy rate was measured from the success rate of artificial insemination. In 14 female Brahman cows divided into two groups. One group of 7 in the artificial insemination with 40002 males with 37.11% sperm DNA damage and one in artificial insemination with 40885 with 10.65% sperm DNA damage. The data obtained were analyzed descriptively by comparing sperm DNA damage with pregnancy rate. The results showed that at 37.11% sperm DNA damage level was found pregnancy rate 57.11% with ultrasound on 30 day and pregnancy rate 42.80% with ultrasound to 45 day. Result of research on sperm DNA damage level of 10.66% found pregnancy rate 57.11% with ultrasound to 30 day and level pregnancy 57.11% with ultrasound 45 days. The results of this study have concluded that there is a difference in the rate of sperm DNA damage with pregnancy rate in Brahman cows. The sperm DNA damage has an effect on pregnancy rate on Brahman cows.